N-terminal region is responsible for mHv1 channel activity in MDSCs - Peña-Pichicoi, Antonio; Fernández, Miguel; Navarro-Quezada, Nieves; Alvear-Arias, Juan J.; Carrillo, Christian A.; Carmona, Emerson M.; Garate, Jose; Lopez-Rodriguez, Angelica M.; Neely, Alan; Hernández-Ochoa, Erick O.; González, Carlos (Frontiers in Pharmacology, 2023)
Voltage-gated proton channels (Hv1) are important regulators of the immunosuppressive function of myeloid-derived suppressor cells (MDSC) in mice and have been proposed as a potential therapeutic target to alleviate dysregulated immunosuppression in tumors. However, up to date, there is a lack of evidence regarding the functioning of the Hvcn1 and reports on mHv1 isoform diversity in mice and MDSC. A computational prediction has suggested that the Hvcn1 gene may express up to six transcript variants, three of which are translated into distinct N-terminal isoforms of mHv1: mHv1.1 (269 aa), mHv1.2 (269+42 aa), and mHv1.3 (269+4 aa). To validate this prediction, by using RT-PCR on total RNA extracted from MDSC, the presence of all six predicted mRNA variance was confirmed. Subsequently, the open reading frames (ORFs) encoding for mHv1 isoforms were cloned and expressed in Xenopus laevis oocytes for proton current recording by macropatch voltage clamp. Our findings reveal that all three isoforms are mammalian mHv1 channels, with distinct differences in their activation properties. Specifically, the longest isoform, mHv1.2, displays a right-shifted GVThis is a provisional file, not the final typeset article curve and slower opening kinetics, compared to the mid-length isoform, mHv1.3, and the shortest canonical isoform, mHv1.1. While mHv1.3 exhibits a V0.5 similar to the V0.5 of mHv1.1, mHv1.3 demonstrates significantly slower activation kinetics than mHv1.1. These results suggest that isoform gating efficiency is inversely related to the length of the N-terminal end. To further explore this, we created the truncated mHv1.2 ΔN20 construct by removing the first 20 amino acids from the Nterminus of mHv1.2. This construct displayed intermediate activation properties, with a V0.5 value lying between those of mHv1.1 and mHv1.2, and activation kinetics that were faster than mHv1.2 but slower than mHv1.1. Overall, these findings indicate that alternative splicing of the N-terminal exon in mRNA transcripts encoding mHv1 isoforms is a regulatory mechanism for mHv1 function within MDSC. While MDSC have the capability to translate multiple Hv1 isoforms with varying gating properties, the Hvcn1 gene appears to promote the dominant expression of mHv1.1, which exhibits the most efficient gating among all mHv1 isoforms.